The Correlation between Students’ Motivation and Their Speaking Achievement at English Department of Halu Oleo University - Wa Ode Fatimah; Firdaus Sale (Journal of English Education and Teaching, 2019)
This research focused on the correlation between students’ motivation and their speaking achievement. The research conducts in Halu Oleo University, English Department at academic year 2017/2018 that have pass Speaking III to see their motivation and speaking achievement. There are 36 students taken as sample. The data of the research collect through close-ended questionnaire adapted from Gardner (1985) who had developed the Attitude/Motivation Test Battery (AMTB) to get the data of students’ motivation index (integrative motivation and instrumental motivation), especially in speaking III. To analyze the data, the researcher uses descriptive statistic to find out the students’ speaking achievement and their motivations based on the five categories of; very good, good, moderate, low and failed. The researcher uses the SPSS 16 program as the statistical program to analyze the data. The finding of the research shows that students’ speaking achievement was mostly categorized as a moderate category and students are moderate motivated in speaking English. The result of inferential statistical analysis show that the result of the Pearson correlation is valued as much as rxy= 0,479 (moderate correlation) with positive significant 0.03(rxy<0.05). Based on the data, the researcher found that there is a significant correlation between students’ motivation and their speaking achievement at English Department of Halu Oleo University. Motivation is an important factor that influenced students’ achievement. Motivation is directly proportional to the score of students. The higher the students’ motivation to speak, the higher their speaking score achieved.